The Implementation Of Verbal Learning Soccer Strategy To Improve Students’ Achievement In Sport Education At The Fifth Grade Students Of Sd Negeri 12 Maredan Barat In Academic Year 2015/ 2016 - Erniati Erniati (Fakultas Sastra Universitas Ekasakti, 2018)
Natural science is closely related to everyday human life, for example, familiar with various energy sources that are often encountered in everyday life and usefulness. A teacher should be able to use strategies that can create conditions and learning situations that enable students to actively shape, discover and develop their knowledge. One of the innovations teachers can make is to use student-centered strategies. A student-centered strategy means that every learning activity can provide the widest possible opportunity for students to be directly involved in the learning process. Based on the background and the above symptoms, it can be formulated the problem in this research as follows: